Microwave-Based Technique for Fast and Reliable Extraction of Organic Contaminants from Food, with a Special Focus on Hydrocarbon Contaminants - Sabrina Moret; Chiara Conchione; Ana Srbinovska; Paolo Lucci (Foods, 2019)
Due to food complexity and the low amount at which contaminants are usually present in food, their analytical determination can be particularly challenging. Conventional sample preparation methods making use of large solvent volumes and involving intensive sample manipulation can lead to sample contamination or losses of analytes. To overcome the disadvantages of conventional sample preparation, many researchers put their efforts toward the development of rapid and environmental-friendly methods, minimizing solvent consumption. In this context, microwave-assisted-extraction (MAE) has obtained, over the last years, increasing attention from analytical chemists and it has been successfully utilized for the extraction of various contaminants from different foods. In the first part of this review, an updated overview of the microwave-based extraction technique used for rapid and efficient extraction of organic contaminants from food is given. The principle of the technique, a description of available instrumentation, optimization of parameters affecting the extraction yield, as well as integrated techniques for further purification/enrichment prior to the analytical determination, are illustrated. In the second part of the review, the latest applications concerning the use of microwave energy for the determination of hydrocarbon contaminants—namely polycyclic aromatic hydrocarbons (PAHs) and mineral oil hydrocarbons (MOH)—are reported and critically overviewed and future trends are delineated.